Penafsiran terhadap Kewenangan Mengatur Pemerintahan Daerah dalam Melaksanakan Urusan Pemerintahan melalui Pembentukan Peraturan Daerah (Interpretation of the Regional Government’s Authority to Regulate in Implementing Government Affairs through the ... ) - Dian Agung Wicaksono; Faiz Rahman (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2020)
The Elucidation of the 2014 Local Government Law has divided the concurrent government affairs between the central government and local governments in detail. To carry out government affairs, local governments have the authority to stipulate regional regulation. The existence of that specific list of concurrent affairs, therefore, raises a question regarding what extent the local government can “elaborates” the government affairs that become their domain in the formulation of regional regulation. This research focuses on two questions: (1) regarding constitutional construction of local government’s authority to regulate; and (2) interpretation of the implementation of the authority to regulate in the formulation of regional regulation. This normative legal research is descriptive, evaluative, and prescriptive in nature. The results indicate alternative interpretations of the authority to regulate, namely implementation in (1) a legalistic-formal approach, through the rigid implementation of the authority and NSPK set by the Government; (2) a normative-extensive approach, by implementing the authority and NSPK, as well as paying attention to the Region’s needs; and (3) a supra-extensive approach, in which the Region goes beyond the corridors of their authority and the NSPK. For this reason, the author suggests that in the formulation of the NSPK, the accuracy of the Central Government is needed, so that can serve as a guideline for implementing flexible government affairs and can accommodate the legal needs of the community in the regions. abstrakLampiran UU Pemda 2014 telah membagi secara detail urusan pemerintahan konkuren antara pemerintah pusat dengan pemerintahan daerah. Untuk melaksanakan urusan pemerintahan konkuren tersebut, pemerintahan daerah memiliki kewenangan untuk menetapkan peraturan daerah. Kehadiran daftar urusan pemerintahan yang spesifik menimbulkan pertanyaan mengenai sejauh mana pemerintahan daerah dapat “menjabarkan” urusan pemerintahan yang menjadi domain kewenangannya dalam pembentukan peraturan daerah. Penelitian ini berfokus pada dua permasalahan, yaitu: (1) konstruksi konstitusional kewenangan mengatur pemerintahan daerah; dan (2) penafsiran terhadap kewenangan mengatur urusan pemerintahan oleh pemerintahan daerah dalam pembentukan peraturan daerah. Penelitian hukum normatif ini dilakukan dengan mengkaji data sekunder, dengan sifat penelitian deskriptif, serta berbentuk evaluatif dan preskriptif. Hasil dari penelitian ini menunjukkan adanya alternatif penafsiran terhadap kewenangan mengatur urusan pemerintahan dalam pembentukan peraturan daerah, yaitu: (1) pelaksanaan kewenangan mengatur secara legalistik-formal, mendasarkan kewenangan dan NSPK yang ditetapkan Pemerintah secara kaku; (2) pelaksanaan kewenangan mengatur secara normatif-ekstensif, yaitu selain mendasarkan pada kewenangan dan NSPK, Daerah juga memperhatikan kebutuhan hukum di Daerah; dan (3) pelaksanaan kewenangan mengatur secara supra-ekstensif, dimana Daerah mengatur melebihi koridor kewenangan dan NSPK. Berdasarkan hasil penelitian ini, disarankan dalam perumusan NSPK diperlukan kecermatan Pemerintah Pusat, sehingga dapat menjadi pedoman pelaksanaan urusan pemerintahan yang luwes dan dapat mengakomodasi kebutuhan hukum masyarakat di daerah.